2014
DOI: 10.1007/s00330-014-3160-7
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion and diffusion characteristics of cervical cancer based on intraxovel incoherent motion MR imaging-a pilot study

Abstract: • Diffusion-weighted MRI is increasingly applied in evaluation of cervical cancer. • Cervical cancer has distinctive perfusion and diffusion characteristics. • Intravoxel incoherent motion characteristics can differentiate cervical cancer from non-malignant uterine tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 19 publications
8
50
1
Order By: Relevance
“…In the conventional segmented biexponential fitting approach with an a priori selected, fixed b-value threshold, D * tended to be “unstable” due to an arbitrarily chosen b-value that did not correspond to the true physical properties of the tissue, because the derived IVIM parameters depend heavily on the b-value threshold used (10). Previously, D * did not even allow for differentiation between normal and cancerous tissue because of its high variability (7). The present finding that the ADC tends to underestimate perfusion restriction is consistent with results of a more extensive study demonstrating that parameters derived from a monoexponential model are clearly inferior in the differentiation of cervical cancer when compared to parameters from biexponential models such as IVIM (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conventional segmented biexponential fitting approach with an a priori selected, fixed b-value threshold, D * tended to be “unstable” due to an arbitrarily chosen b-value that did not correspond to the true physical properties of the tissue, because the derived IVIM parameters depend heavily on the b-value threshold used (10). Previously, D * did not even allow for differentiation between normal and cancerous tissue because of its high variability (7). The present finding that the ADC tends to underestimate perfusion restriction is consistent with results of a more extensive study demonstrating that parameters derived from a monoexponential model are clearly inferior in the differentiation of cervical cancer when compared to parameters from biexponential models such as IVIM (16).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the signal decay is described by a biexponential instead of a monoexponential equation which yields a more accurate description of the underlying tissue properties (5). IVIM has recently been shown to differentiate among histopathological tumor types, and, in addition, correlates with tumor grades of cervical cancer (67). …”
Section: Introductionmentioning
confidence: 99%
“…For example, intravoxel incoherent motion (IVIM) is an imaging technique for the separate estimation of tissue perfusion and diffusivity using multi-b-value DWI [18, 20]. It has been shown that perfusion fraction of IVIM reflected microvessel density in different tumors [19, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown lower ADCs in poorly differentiated tumours than in well/moderately differentiated tumours, but attempts to distinguish between squamous cell carcinoma and adenocarcinoma using ADC estimates have yielded mixed results [21, 22]. Use of a bi-exponential model has indicated a lower perfusion fraction ( f ) and diffusion coefficient (D) in cervical tumours than in normal cervix [23]. Assessment of the relationships between fitted parameters of DW-MRI models and tumour histopathology would establish the ability of a model to detect differences between grades and types of tumour, and the potential to detect treatment effects that may not be described by the ADC derived from the mono-exponential model.…”
Section: Introductionmentioning
confidence: 99%